Pengaruh Edukasi Metode Ceramah dan Media Leaflet Terhadap Tingkat Pengetahuan Tuberkulosis Paru pada Remaja di SMP Gunungjati Kembaran - Elvina Vershinta; Ikit Netra Wirakhmi; Maya Safitri (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Pulmonary Tuberculosis (Pulmonary TB) is a contagious infection that attacks the lungs and remains a public health issue, including among adolescents. Low levels of knowledge regarding Pulmonary TB can increase the risk of disease transmission. This research seeks to analyze the impact of educational interventions using lecture strategies and leaflets on the level of knowledge about Pulmonary TB among adolescents at SMP Gunungjati Kembaran. A pre-experimental method involving a onegroup pretest-posttest design was implemented in this research utilizing 64 samples selected through a total sampling technique. Data collection utilized a validated questionnaire on Pulmonary TB knowledge levels. Data processing included univariate and bivariate analysis using the Wilcoxon test. The results showed an increase in the average knowledge level of respondents after being given education. The average knowledge level before the intervention (pretest) was 47.84 and increased to 74.81 after the intervention (posttest). Based on statistical tests, a p-value of 0.001 (p < 0.05) was obtained, indicating a significant influence of the lecture method and leaflet media on the knowledge level of Pulmonary TB in adolescents. Thus, health education through lectures and leaflets has a significant impact on increasing knowledge about Pulmonary TB in adolescents and is recommended for continuous implementation as part of health promotion programs in school environments.